Analisis Metode Apriori Untuk Memprediksi Persediaan Barang Pada Warung - Wulan Dari (Yayasan Literasi Sains Indonesia, 2022)
The data processing system in the shop is still manual. Previously, the shop had not been able to predict the stock or inventory of goods. Therefore, this system predicts the inventory of goods in the shop. so that the data processing system at the shop can be handled by problems that occur and can form information quickly, precisely, and well. The use of the a priori method which will be used to calculate the prediction of the supply of goods in stock that is still there. And this a priori method will later be used to calculate odds. Data storage using SQL Server database. With the development of technology, the ability to collect and process data is also growing. Data processing has become the advantage of computers, computers have also penetrated various aspects, both in the field of education and in the business world. Competition in the global business has built tight competition between one stall and another. This algorithm is used to analyze when purchasing goods that have run out of stock by classifying which goods have been added to stock or not, as a result, the availability of goods remains stable and maintained. The author is currently making inventory predictions at the stalls to develop an existing system with the a priori method.